Sistem Pakar Mendiagnosa Penyakit Difteri Pada Anak dengan Menggunakan Metode Certainty Factor - Elfryda Sinaga (BEES: Bulletin of Electrical and Electronics Engineering, 2020)
Diphtheria is now common among the general public, especially children who are very susceptible to various diseases. Diphtheria disease can cause death to anyone if it is not immediately treated medically. The spread of diphtheria is caused by corynebacterium bacteria through the air or physical contact by the sufferer. There are several early symptoms that can be recognized such as fever accompanied by chills, nasal congestion or a runny nose, but these symptoms are almost the same as the symptoms of tonsillitis, which also has the same symptoms as diphtheria. Apart from the symptoms caused by diphtheria there are also several factors that affect the disease such as; lack of maintenance of environmental cleanliness, wrong food intake, lack of nutritious food and so on. This is what causes the medical team to have difficulty diagnosing diphtheria in children. Therefore, the authors use an expert system by applying the certainty factor method to diagnose diphtheria. Through the application of this method is expected to be able to provide diagnosis of diphtheria and provide definite information about the possibility of a patient being diagnosed with diphtheria according to experts